SEARCH FOR A SOURCE OF TRITERPENE ACIDS IN RUSSIAN BIRCHES - Vedernikov, Dmitriy Nikolayevich; Eregina, Ol’ga Alekseyevna; Shemyakina, Anna Viktorovna (Химия растительного сырья, 2020)
The composition of triterpene acids and triterpene alcohols of the outer bark of a damaged silver birch tree (Betula pendula Roth.) the outer bark of silver birch branches, the outer bark of Betula davurica Pall., B. mandshurica (Regel) Nakai, B. platyphylla Sucacz. and B. costata Trautv. is considered. Silver birch bark was harvested in the Leningrad region. The bark of other species of birches was harvested in the Khabarovsk region. The qualitative composition of triterpene compounds was determined by chromatography-mass spectrometry. The quantitative composition was determined by gas-liquid chromatography and absolute calibration. Butyl esters of acids were preliminarily prepared for GLC analysis of triterpene acids. The outer bark of the eastern species of birches contains significantly more betulinic and oleanolic acid than silver birch. The relative content of triterpene acids is greater in the outer bark of branches and in the bark of damaged silver birches. The increase in acid content is apparently associated with the desire to heal a wound. The main component among the triterpenoids of the investigated raw materials is betulin. For the separation of acids from other triterpenoids, various solubilities of the compounds in solvents and the ability of acids to form poorly soluble salts were used.